An Integrated Control Theory Model of Work Motivation - Klein, Howard J. (Academy of Management Review, 1989)
A model that integrates several different motivational theories and previous control theory models is presented as a possible meta-theory to focus future theoretical and empirical efforts. The proposed model is dynamic, parsimonious, and focuses on self-regulation and the underlying cognitive mechanisms of motivation. In explicating this model, numerous hypotheses are derived regarding (a) the nature of goals and feedback; (b) cognitive, behavioral, and affective reactions to goals and feedback; and (c) the role of attributions, expectancies, and goal hierarchies in determining those reactions.